2020
DOI: 10.3390/microorganisms8081160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymol Supplementation on Goat Rumen Fermentation and Rumen Microbiota In Vitro

Abstract: This study was performed to explore the predominant responses of rumen microbiota with thymol supplementation as well as effective dose of thymol on rumen fermentation. Thymol at different concentrations, i.e., 0, 100 mg/L, 200 mg/L, and 400 mg/L (four groups × five replications) was applied for 24 h of fermentation in a rumen fluid incubation system. Illumina MiSeq sequencing was applied to investigate the ruminal microbes in addition to the examination of rumen fermentation. Thymol doses reached 200 mg/L and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 87 publications
0
15
0
1
Order By: Relevance
“…Shen, Liu, Yu (39) reported that monensin and nisin supplementation decreased the absolute abundance of total bacteria and overall rumen fermentation (gas and VFA production) with a concomitant change in the major rumen microbiota. The supplementation of plant secondary metabolites such as thymol and oregano oil has recently shown to change the major microbiota with a concomitant reduction in feed digestion and rumen fermentation [38,40]. In the present study, endolysin LyJH307 did not affect the absolute abundance of total bacteria, ciliate protozoa (Table 3) and major microbiota from phylum to genus levels (having relative proportions > 1%) ( Figure 4).…”
Section: Discussionmentioning
confidence: 38%
“…Shen, Liu, Yu (39) reported that monensin and nisin supplementation decreased the absolute abundance of total bacteria and overall rumen fermentation (gas and VFA production) with a concomitant change in the major rumen microbiota. The supplementation of plant secondary metabolites such as thymol and oregano oil has recently shown to change the major microbiota with a concomitant reduction in feed digestion and rumen fermentation [38,40]. In the present study, endolysin LyJH307 did not affect the absolute abundance of total bacteria, ciliate protozoa (Table 3) and major microbiota from phylum to genus levels (having relative proportions > 1%) ( Figure 4).…”
Section: Discussionmentioning
confidence: 38%
“…The results of IVTDMD and IVTOMD revealed that EO has a depressive effect on the rumen microbial activity and in consequence on ruminal digestibility at 450 and 600 mg/L levels. Earlier studies have shown that essential oils have a typically dose-dependent effect on rumen fermentation with a specific selective effect at low and moderate, and a general inhibitory effect at high doses that generally varies depending on the type of the essential oil (Hart et al, 2008;Yadeghari et al, 2015;Yu et al, 2020). In this connection, Benchaar et al (2007) found that carvacrol reduces ruminal digestibility at doses higher than 400 mg/L in vitro.…”
Section: -H In Vitro Ruminal Fermentation Digestibility and Methane Productionmentioning
confidence: 98%
“…Among a vast array of phytochemicals tested in vitro, including essential oils, plant extracts or their individual bioactive compounds, many of them have reduced ruminal methane production (El-Zaiat and Abdalla, 2019;Joch et al, 2019;Yu et al, 2020). However, it is important to notice that in many cases, methane inhibition by phytochemicals has been accompanied with a concomitant decrease in ruminal DM and OM digestibility (Oskoueian et al, 2013;Joch et al, 2019;Garcia et al, 2020).…”
Section: -H In Vitro Ruminal Fermentation Digestibility and Methane Productionmentioning
confidence: 99%
“…Pyramidobacter was found in nonextracted acacia only. Fretibacterium has the adaptability to phenolic compounds that might explain the prevalence of this genus in non-extracted acacia (Evans and Martin, 2000;Yu et al, 2020). Additionally, genus Pyramidobacter detoxifies toxic compounds found in many plant species including acacia.…”
Section: Nd=non-determinedmentioning
confidence: 99%